1994
DOI: 10.1111/j.1476-5381.1994.tb14806.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanism of [3H]‐noradrenaline release from SH‐SY5Y cells: the role of Ca2+ and cyclic AMP

Abstract: 1 The roles of both Ca2`and adenosine 3':5'-cyclic monophosphate ( 5 These data suggest that in SH-SY5Y cells, elevated cyclic AMP levels are not directly involved in [3H]-noradrenaline release. In addition, carbachol-stimulated release is largely independent of extracellular Ca24 possibly implying a role for intracellular stored Ca24 in the release process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Depolarization with K+ dose-dependently stimulated Ins(1,4,5)P3 formation, with an EC50 of 47 mM. This doseresponse to K+, whilst appearing weak, is consistent with our previous studies of K+-stimulated noradrenaline release (63 mM) and adenosine 3':5'-cyclic monophosphate (cyclic AMP) formation (49 mM) (Atcheson et al, 1994), as well as the K+-induced increase in [Ca2+]i (50 mM) in the present study, indicating the importance of Ca2+ in cross-talk between second messenger systems. K+-depolarization also increased [Ca2+]I, in a dose-dependent manner, by opening VSCCs and so allowing Ca21 influx.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Depolarization with K+ dose-dependently stimulated Ins(1,4,5)P3 formation, with an EC50 of 47 mM. This doseresponse to K+, whilst appearing weak, is consistent with our previous studies of K+-stimulated noradrenaline release (63 mM) and adenosine 3':5'-cyclic monophosphate (cyclic AMP) formation (49 mM) (Atcheson et al, 1994), as well as the K+-induced increase in [Ca2+]i (50 mM) in the present study, indicating the importance of Ca2+ in cross-talk between second messenger systems. K+-depolarization also increased [Ca2+]I, in a dose-dependent manner, by opening VSCCs and so allowing Ca21 influx.…”
Section: Discussionsupporting
confidence: 91%
“…We show here that depolarization with high extracellular K+ opens L-type VSCCs, allowing Ca2+ influx to activate PLC, resulting in increased Ins(1,4,5)P3 formation, in a homogeneous neuronal preparation. Although SH-SY5Y cells release noradrenaline when stimulated with high K+ (Atcheson et al, 1994), these cells do not possess PLC-coupled ocl-adrenoceptors, only a2-receptors, which do not couple to polyphosphate turnover (Smart et al, 1995). Therefore, the activation of PLC by K+ must occur via a non-receptormediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…may reach 200-300 ACM (Llinas et al ., 1992) . However, instances of regulated exocytosis of neurotransmitters after activation of G protein-linked receptors that are independent of extracellular Ca 2' have been documented in PC12, NG108-15, chromaffin, and SH-SY5Y cells (Appel] and Barefoot, 1989 ;Ogura et al ., 1990 ;Augustine and Neher, 1992 ;Vaughan et al ., 1993a ;Atcheson et al, 1994) . Such stimulation of exocytosis is likely to be mediated via Ca"' released from intracellular stores by inositol 1,4,5-trisphosphate [Ins (1,4,5) P 3 ] after activation of phospholipase C (PLC) .…”
mentioning
confidence: 99%
“…We have reviously reported that ketamine selectively inhibits K' evoked [-Hlnoradrenaline release from SH-SY5Y cells with an IC,, of 170pM [2]. As K' evoked release is entirely extracellular Ca" dependent [3] our data infer that ketamine inhibits Ca2' influx through voltage sensitive Ca" channels in these cells In this study we have examined the effects of ketamine on K' stimulated increases in [CaZL], in fura-2 loaded cells P Confluent SH-SY5Y cells (maintained as described previously [3]) were harvested and resuspended in KrebskIEPES buffer, pH 7.4 containing 3pM fura-2 AM The cell suspension was then incubated for 30 minutes at 37°C followed by a postincubation of 20 minutes at room temperature Fluorescence was measured using a Perkin-Elmer LSSOB fluorimeter with excitation wavelengths set at 340 and 380nm. Emission was measured at 510nm [4] lntracellular Ca2' was calculated from the 3401380 excitation ratio according to Grynkiewicz et al (1985) [S] La, and L,, were determined using Triton X-100 (0.1%) and EGTA (4 5mM pHX.0).…”
mentioning
confidence: 99%